2022
DOI: 10.15252/msb.202110407
|View full text |Cite
|
Sign up to set email alerts
|

Distinct transcription kinetics of pluripotent cell states

Abstract: Mouse embryonic stem cells (mESCs) can adopt naïve, ground, and paused pluripotent states that give rise to unique transcriptomes. Here, we use transient transcriptome sequencing (TT‐seq) to define both coding and non‐coding transcription units (TUs) in these three pluripotent states and combine TT‐seq with RNA polymerase II occupancy profiling to unravel the kinetics of RNA metabolism genome‐wide. Compared to the naïve state (serum), RNA synthesis and turnover rates are globally reduced in the ground state (2… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1

Citation Types

0
3
0

Year Published

2022
2022
2024
2024

Publication Types

Select...
7
1

Relationship

0
8

Authors

Journals

citations
Cited by 9 publications
(3 citation statements)
references
References 109 publications
0
3
0
Order By: Relevance
“…To study antisense transcription beyond annotated genes, we first assembled a nascent transcriptome annotation for each time point from scratch (Fig. 3A, see methods for details), as done previously for such data (Shao et al , 2022). We segmented the genome into transcribed and non-transcribed 200 bp fragments for each strand.…”
Section: Resultsmentioning
confidence: 99%
“…To study antisense transcription beyond annotated genes, we first assembled a nascent transcriptome annotation for each time point from scratch (Fig. 3A, see methods for details), as done previously for such data (Shao et al , 2022). We segmented the genome into transcribed and non-transcribed 200 bp fragments for each strand.…”
Section: Resultsmentioning
confidence: 99%
“…In mammalian single-cell sequencing studies, RNA spike-ins have demonstrated the presence of hypertranscription states, where cells undergo global transcriptional upregulation (Kim et al, 2023;Percharde et al, 2017). RNA spike-ins have also been successfully used to control for differences in transcriptome size, for example, in maturing oocytes (Wu, 2022) and pluripotent states (Shao et al, 2022). Further complicating single-cell RNA-Seq analysis, in mammalian cells, significant variation in the number of mRNA per cell is observed due to bursts of active transcription periods (Raj et al, 2006).…”
Section: The Implication Of Rna Spike-in Controls In Rna-seq Normaliz...mentioning
confidence: 99%
“…A transitional formative state that is germ cell competent can also be captured (42). It was recently reported that RNAPII elongates slower in 2i/LIF conditions (43). We passaged serum/LIF ESCs, in which all the preceding experiments were performed, into either 2i/LIF or formative conditions (fig.…”
Section: Escs Have Greater Rnapii Elongation As Compared To Somatic C...mentioning
confidence: 99%